2016
DOI: 10.1039/c6cp03564g
|View full text |Cite
|
Sign up to set email alerts
|

Identifying short surface ligands on metal phosphide quantum dots

Abstract: The control and understanding of the chemical and physical properties of quantum dots (QDs) demands detailed surface characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 55 publications
(47 reference statements)
1
26
1
Order By: Relevance
“…As we have recently demonstrated, this 31 PO 4 phosphate signal results from the overlap of the resonances of several phosphate species: O=P(OM) x (OH) 3-x (M=In, x=1-3). 22 For the example shown in Figure 1b, this yielded only 2% of oxidized phosphorous. This result confirms previous studies that showed that the aminophosphinebased protocol allows oxide-free InP QDs to be made, thanks to the use of water-and carboxylate-free precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have recently demonstrated, this 31 PO 4 phosphate signal results from the overlap of the resonances of several phosphate species: O=P(OM) x (OH) 3-x (M=In, x=1-3). 22 For the example shown in Figure 1b, this yielded only 2% of oxidized phosphorous. This result confirms previous studies that showed that the aminophosphinebased protocol allows oxide-free InP QDs to be made, thanks to the use of water-and carboxylate-free precursors.…”
Section: Resultsmentioning
confidence: 99%
“…A more detailed description of this interface results from a 1 H Forth and Back Cross Polarization (FBCP) MAS NMR experiment. 22 Such a measurement relies on the transfer of polarization from H atoms that are part of the stabilizing ligand to the P atoms at the QD and back to the closest H atom. In this way, we can detect P-OH species that are usually invisible with the classical 1 H MAS NMR techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Although HETCOR is powerful, the experiment is also time‐consuming. Recently, Delpech and co‐workers proposed the use of a Forth and Back CP experiment (FBCP), in which polarization is transferred from the hydrogen to the phosphorus atoms of an NC and back to the hydrogen atoms . Thus, it was possible to probe the hydrogen atoms selectively, on and close to the phosphorus atom at the NC surface.…”
Section: Resultsmentioning
confidence: 99%
“…Recently,D elpech and co-workersp roposed the use of aF orth and Back CP experiment (FBCP), in which polarization is transferred from the hydrogen to the phosphorus atoms of an NC and back to the hydrogen atoms. [29] Thus,i tw as possible to probe the hydrogen atoms selectively,o na nd close to the phosphorus atom at the NC surface. In our case of HfO 2 NCs, the inorganic core does not contain any abundant NMR-sensitive nucleus, hampering the technique.…”
Section: Generalization To Hfo 2 Ncsmentioning
confidence: 99%
“…Other types of ligands have also been studied on nanoparticles . Gullion and co‐workers used 13 C– 15 N REDOR to determine the adsorption configuration of L ‐cysteine on gold nanoparticles.…”
Section: Interfaces In Nanocrystals and Quantum Dotsmentioning
confidence: 99%